Analysis Of the Ripping Rate of Banana Fruit Coated with Biofilm Based on Polyvinyl Alcohol Chitosan Composite - Amiati, Meli; Paramita, Indira; Kanani, Nufus; Wardoyo, Endarto Yudo; Kustiningsih, Indar (Universitas Sultan Ageng Tirtayasa, 2023)
The Banana (Musa spp) was a fruit whose rate of ripening increased after harvest. The respiration rate was an indicator of the fruit’s shelf life. This cause banana to have a short shelf life and become easily damaged, necessitating the technology to reduce the ripening rate of fruit, such as coating it with biofilm. This research seeks to establish the optimal ethylene concentration on the composite chitosan PVA produced by evaporation of a colloidal chitosan solution with CNC. The produced solution was then applied to the surface of the banana using the immersion method, and seven-day changes in weight loss, color change, sugar content, and ethylene gas production were detected. Post-harvest management of bananas tries to preserve the fruit’s freshness and shelf life. The research is done to improve the shelf life of bananas by composite biofilm. The data result shows that from all variants, the composite biofilm contains chitosan, PVA, 10% glycerol, Citric acid, and 5% CNC, which is indicated to have the potential to increase the shelf life of banana fruit. Because they prevent respiration and the water evaporation processes in bananas, these properties allow banana fruits to stay fresh longer.